2019
DOI: 10.1002/anie.201812878
|View full text |Cite
|
Sign up to set email alerts
|

Precise In Vivo Inflammation Imaging Using In Situ Responsive Cross‐linking of Glutathione‐Modified Ultra‐Small NIR‐II Lanthanide Nanoparticles

Abstract: To improve the bioimaging signal-to-noise ratio (SNR), long-term imaging capability,a nd decrease the potential biotoxicity,aninvivo cross-linking strategy was developed by using sub-10 nm, glutathione-modified, lanthanide nanoprobes.A fter administration, the nanoprobes cross-link in response to reactive oxygen species (ROS) at the inflamed area and enable the quicki maging of ROSi nt he second nearinfrared (NIR-II) window.These nanoprobes could be rapidly excreted due to their ultra-small size. This strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(110 citation statements)
references
References 66 publications
(19 reference statements)
1
107
1
1
Order By: Relevance
“…[1][2][3][4] Therefore, it requires effective imaging tools to assess the progression of diseases and their therapeutic response. [7][8][9][10][11] To date, compared to fluorescence imaging in the visible and nearinfrared wavelengths (<900 nm), deep tissue imaging in the second near-infrared window (NIR-II, 1000-1700 nm) has benefited from negligible tissue autofluorescence and scattering, leading to superior improvements in higher resolution and fidelity. [5,6] As a promising candidate of imaging modality with respect to noninvasive and nonradiation, optical imaging has been an area of intense focus in real-time visualization and monitoring the dynamic pathological processes of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Therefore, it requires effective imaging tools to assess the progression of diseases and their therapeutic response. [7][8][9][10][11] To date, compared to fluorescence imaging in the visible and nearinfrared wavelengths (<900 nm), deep tissue imaging in the second near-infrared window (NIR-II, 1000-1700 nm) has benefited from negligible tissue autofluorescence and scattering, leading to superior improvements in higher resolution and fidelity. [5,6] As a promising candidate of imaging modality with respect to noninvasive and nonradiation, optical imaging has been an area of intense focus in real-time visualization and monitoring the dynamic pathological processes of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies in this field include Zhao et al (2019) which reported on an original method for the accurate imaging of inflammation in vivo using in situ cross bonding of glutathione-combined ultrafine lanthanum nanoparticles with NIR-II fluorescent emission. Although nanoprobes have been proven to be promising bioimaging platforms by reason of their EPR effects, to the inability to enrich nanoprobe at target position has been a key bottleneck to improve detection ability and effect.…”
Section: Medical Testingmentioning
confidence: 99%
“…Wang et al. prepared NIR‐light‐responsive I/ D ‐Se‐NPs, and these polymers could form nanoscale micelles loaded with ICG and DOX (Scheme C) . Under λ =808 nm laser irradiation, the polymeric NPs were rapidly dissociated due to selenium oxidation caused by generated ROS.…”
Section: Stimuli‐responsive Drug‐release Nanosystemsmentioning
confidence: 99%